PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN APLIKASI KODULAR UNTUK MENGIDENTIFIKASI RESPON SISWA - Moh Mahfud Effendi; Hendarto Cahyono; Siti Khoiruli Ummah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
Learning in post-pandemic schools is experiencing a transition where students are used to operating gadgets for learning while teachers are inexperienced in developing application-based media. In addition, students are also not used to solving AKM types of questions. Therefore, this study aims to describe the development of learning media using codular applications to identify student responses in solving AKM questions contained in the media. This study uses a 4D development model with a limited stage of disseminating development results. The test subjects of this study were junior high school students where the test data obtained was analyzed qualitatively from the response results after operating the media. The results of the research show that at the defining analysis stage it is done by distributing online questionnaires to teachers. The results of the questionnaire show that schools need learning media so that mathematics learning is integrated with technology. The learning media should be practical to learn and access anywhere and anytime. This resulted in the selection of learning media to be application-based and accessible through student gadgets. Next, at the design stage. Next, look for references about using Kodular applications and designing media. The results of the validation show that the media is feasible to be tested on students. Media trials as a development stage show a variety of responses. The results of identifying student responses based on questionnaires show that students like application-based learning media because they are easy to operate and practical to use for learning on various occasions. Students also stated that all navigation buttons function properly and the layout is consistent. The dissemination stage was carried out by training teachers in making application-based learning media and the result was that 2 teachers produced media.